Typewriting as War Machine: Robert Duncan between Self- and Anti-Publishing - Clément Oudart (IdeAs)
Even if publishing one’s poetic works with New Directions, James Laughlin’s New-York-based publishing house, is still seen by many in the experimental poetry world as the ultimate accolade, underground alternatives turn out to have been even more appealing to a marginal figure like the Bay Area poet Robert Duncan (1919-1988). A quick glance at the author’s bibliography unravels striking shifts in his publishing policy. Before and between his major New Direction volumes, the poet produced a whole series of small, hardly circulated chapbooks. These small publications not only reflect his commitment to the small press scene, but also convey a forceful point about the writer’s autonomy from the empire of publishing.